2020
DOI: 10.5152/j.aott.2020.20092
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after the surgical treatment of the Dubberley type B distal humeral capitellar and trochlear fractures with a buttress plate

Abstract: Relationship between the tilt angle of bipolar radial head prostheses and radiological radiocapitellar instability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although Kirschner wires have been found to provide lower functional outcomes compared with screws, they are an option, particularly in cases characterized by small fracture fragment size [ 64 , 65 ]. They can be used either isolated or in association with other methods, such as external fixation [ 66 , 67 ]. Threaded Kirschner wires are preferred to smooth ones to minimize the risk of migration.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Kirschner wires have been found to provide lower functional outcomes compared with screws, they are an option, particularly in cases characterized by small fracture fragment size [ 64 , 65 ]. They can be used either isolated or in association with other methods, such as external fixation [ 66 , 67 ]. Threaded Kirschner wires are preferred to smooth ones to minimize the risk of migration.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%
“…Even if proper treatment with the plate is performed, posterior comminution can be associated with worse clinical results, as compared to Dubberley subtype A fractures [ 69 ]. A lateral buttress plate can be helpful in cases when comminution is more lateral than posterior [ 25 , 66 , 70 ]. Moreover, lateral placement of the plate avoids posterior stripping of the humeral surface.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jupiter 4 Anterior view of a group PLP specimen after cyclic loading and load to failure testing with the capitellum fragment's proximal displacement et al found that restoration of normal anatomy correlates with elbow joint function at the humeral distal frontal plane [12]. Thus, the basic surgical aim of this particular type of fracture's osteosynthesis is to restore anatomical integrity of the fragments, achieve lateral column stability, prevent interfragmentary rotation, and establish adequate support at the distal humerus [6].…”
Section: Discussionmentioning
confidence: 99%
“…Anteroposterior headless compression screws demonstrated favorable outcomes for the treatment of coronal plane fractures [8,15,17,23,28]. However, it is an appropriate technique for simple fractures, but inadequate for the management of Dubberley type B fractures, mostly including multiple fragments at the posterior part of the distal humerus and at the lateral capitellar area where the LCL adheres [6,33]. Mighell et al previously reported that if no adequate subchondral bone stock is available, iatrogenic fractures may also occur [17].…”
Section: Discussionmentioning
confidence: 99%